PERAN POLITIK KYAI DI MASYARAKAT (Studi Tentang Bentuk dan Variasi Peran Politik Kyai di Pedesaan) - Luluk Maktumah (Jurnal Ilmiah Ar-Risalah: Media Ke-Islaman, Pendidikan dan Hukum Islam, 2016)
The study of the role of clerics in society has manyconducted by researchers. Both the typology and variationsforms of political involvement in rural communities. Studies onthese clerics interesting to talk about at least since two reasons:(1) The difference of understanding of clerics still occur amongresearchers; (2) The modernization process has seen lowertheir roles and functions as a character kyais religion in society.In any event, the involvement of clerics is needed in thecommunity because sociologically kyais is part of the religiouslife. The study discusses typology clerics and other forms ofinvolvement in politics in rural communities. Kyai can becategorized not just as spiritual religious scholars, clericsadvokatif, adaptive and political clerics political clerics criticalpartners, as expressed by the Imam Suprayogo, but alsoclerics and religious scholars nasab fate, seen from In terms ofhis descendants and spiritual religious scholars, clericsmovements, political clerics accommodating pragmatic andideological clerics accommodative political views in terms ofactivity and political affiliation in the community.